Level of Growth and Accounting Profitability in Corporate Value Creation Strategy - Erni Ekawati (The Indonesian Journal of Accounting Research, 2013)
This research examines associations between level of growth and accounting profitability drawn from corporate value creation strategy. Results demonstrate that although the accounting profitability measures generally rise with sales growth, an optimal point exists beyond which further growth contributes to value destruction and adversely affects profitability.